Blood Pressure, not Heart Rate, as a Marker of Intravascular Injection of Epinephrine in an Epidural Test Dose. Issue 5 (September 1991) - Kahn, Richard L.; Quinn, Thomas J.
Abstract : Investigators have generally examined the heart rate response after injection of a test dose containing a β-adrenergic agonist as an indicator of intravascular placement of an epidural catheter. Some have reported an increase in blood pressure accompanying the increase in heart rate after an intravascular injection. We report two-elderly patients (aged 76 and 62 years, respectively) in whom apparent intravascular injections of epinephrine-containing local anesthetic solutions resulted in marked blood pressure elevations without noticeable increases in heart rate. As far as we know, this phenomenon previously has been described only in patients receiving β-adrenergic blocking drugs. In these patients it may be related to decreased β-adrenergic receptor responsiveness in elderly patients; this and other possible mechanisms are discussed.